ANALISIS DAYA SAING KOMODITAS KAYU MANIS JAMBI (Pendekatan Policy Analysis Matrix) - Suandi; Nopi, Sukris; Fathoni, Zakky (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
The purposes of the study are : (1) to tind out general description of cinnamon farming Jambi,(2) to find out the comvetitiveness of cinnamon farming Jambi,(3) to find out impact the government policy toward output, input, input-output of cinnamon farming Jambi. Desaign of research is cross sectional. This research held in Gunung Raya District Kerinci, with total sample as much 82 farmers. Analysis method used approach Policy Analysis Matrix (PAM). The result of research indicate in the cinnamon farming is already in accordance with predetermined standards and intensification is needed on cinnamon farming.The cinnamon farming in the research area has competitive our the value Domestic Resource Cost Ratio (DRCR), and value of Private Cost Ratio (PCR) are less than one, 0,6735 and 0,6845 consequently. Throught PAM result, the impact of government policy in the output, input, input-output that the producer receives a price less than the price that should be received, subsidy and government protection against foreign input used, where as policy government toward input-output not effectively where is the profits obtained by farmers are smaller social benefits, so that farmers spent production costs greater than social costs used.